Analisis Laporan Keuangan Menggunakan Metode Vertikal Dan Horizontal Untuk Mengevaluasi Kinerja Keuangan Pada PT. Mandom Indonesia Tbk - Ratih Purwasih; Aris Munandar (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This type of research is a qualitative descriptive research. The purposes of this research are (1) to find out and analyze financial performance based on vertical analysis of PT. Mandom Indonesia, Tbk, (2) To find out and analyze financial performance based on horizontal analysis of PT. Mandom Indonesia Tbk. The population in this study is the financial statements of PT. Mandom Indonesia Tbk for 20 years with a sample of 7 years. The results of the vertical analysis of PT. Mandom Indonesia, Tbk from 2015-2021 has been optimal. This can be seen from the total assets post which is greater than the total liabilities post. As for the vertical analysis of the profit and loss report, it shows that it is not optimal because of the large operating expenses which have experienced a significant increase and have affected operating income. It can be concluded that the financial performance of PT. Mandom Indonesia, Tbk optimal. And the results of horizontal analysis of PT. Mandom Indonesia, Tbk from 2015-021 has experienced a negative trend in its total assets, because it has decreased every year. On the total liabilities and equity of PT. Mandom Indonesia, Tbk is also experiencing a negative trend because it has decreased every year. Then in the 2015-2021 profit and loss report with a negative trend because the company's total revenue has decreased very significantly. Likewise, operating profit experienced a negative trend due to an increase in expenses that was greater than the increase in income, so that based on horizontal analysis the income statement still tended to be not optimal.